2013
DOI: 10.4314/ahs.v13i2.11
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS knowledge among undergraduate university students: implications for health education programs in Ghana

Abstract: Background: Globally, the spread of HIV/AIDS remains on the rise especially among adolescents who are at increased risk of infection. Sexual behavioural change remains one of the most effective ways of preventing further transmission among this vulnerable group. Objective: To evaluate HIV/AIDS knowledge among undergraduate students' and how it can be used in HIV prevention strategies in Ghana. Methods: A cross-sectional study was conducted using structured questionnaires among 324 conveniently selected student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
6
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 19 publications
8
38
6
2
Order By: Relevance
“…This is in agreement with the result of the study carried out in Shanghai China [16][19] [22] but this was not synonymous with the findings of study conducted in Kwara state of Nigeria [10] . The acceptance of HCT was high among participants which is similar to the result of studies conducted in other regions in Africa [12][14] [17] and Ethiopia [4] . Result from this study showed that high acceptance HCT was seen among female.…”
Section: Discusionsupporting
confidence: 77%
“…This is in agreement with the result of the study carried out in Shanghai China [16][19] [22] but this was not synonymous with the findings of study conducted in Kwara state of Nigeria [10] . The acceptance of HCT was high among participants which is similar to the result of studies conducted in other regions in Africa [12][14] [17] and Ethiopia [4] . Result from this study showed that high acceptance HCT was seen among female.…”
Section: Discusionsupporting
confidence: 77%
“…Fifty one included studies assessed the awareness of 1,235,811 Africans in regard to HIV in total of 35 countries, eleven studies were conducted in Nigeria [14,16,83,17,18,23,38,48,60,63,81] , nine in South Africa [24,27,29,34,37,42,46,82,84] , five in each of Ghana [19,31,65,66,68] and Ethiopia [21,73,77,78,80] , four in Uganda [13,55,72,75] , three in Mozambique [22,26,30] , two in each of Namibia [45,76] and Cameroon [59,67] , one in each of Congo [25] , Sudan [33] , Senegal [39] , Morocco [47] , Gambia [50] , Tanzania [53] , Madagascar [71] and Egypt [74] while a study provided awareness prevalence in 33 countries [8] . The conduction of the studies ranged from 2010 to 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Universities have investigated various aspects of targeted interventions to increase the effectiveness of HIV prevention training programmes, but ongoing research is needed to ensure that intervention programmes remain suitable and novel (Agardh, CantorGraae & Ö stergren 2012;Blignaut, Vergnani & Jacobs 2014;Durojaiye 2011;Mutinta, Govender, Gow & George 2012;Oppong & Oti-Boadi 2013).…”
Section: Introductionmentioning
confidence: 99%